Analisis Pengaruh Daya Dukung Tanah Terhadap Indek Tebal Perkerasan Jalan Menggunakan Metode Bina Marga - Rene Clinton da Costa Soares; Putu Budiarnaya (Universitas Pendidikan Nasional, 2020)
The carrying capacity of the subgrade in road construction is one of the factors that is very instrumental in determining the strength of the construction of the road. The carrying capacity of subgrade is strongly influenced and determined from the CBR value of the soil. The carrying capacity of subgrade is obtained through the DDT and CBR correlation graphs. The greater the CBR value of subgrade in road construction and the greater the carrying capacity of the land from the road. The pavement thickness index (ITP) is a value that functions to determine the thickness of each pavement layer. The value of pavement thickness index will vary greatly and will greatly affect the amount of carrying capacity of the soil. The pavement thickness index is obtained through the relationship between the carrying capacity of the soil (DDT), Cross Equivalent Plan (LER) and regional factors (FR). This value is obtained through the nomogram that has been provided in the Highway Flexible Pavement Pavement Thickness Planning manual with the Bina marga component analysis method. This study aims to determine the relationship (correlation) between the carrying capacity of the soil with the value of the road pavement thickness index using the bina marga method and knowing how much influence the carrying capacity of the soil on the road pavement thickness index. From the analysis results obtained a comparison value of each value that has been determined through reading the Scatter diagram of the relationship between DDT and ITP. From the Scatter reading the relationship diagram (correlation) between the carrying capacity of the soil (DDT) and the pavement thickness index (ITP) is linear negative at all points of value, because the two relations run very strongly / negatively opposite because the correlation results (r = - 0.993909289 approaching - 1). Therefore, the greater the carrying capacity of the soil (DDT), the smaller the thickness of the pavement index produced or the greater the carrying capacity of the soil (DDT), the smaller the thickness of the resulting pavement layer. From the carrying capacity of the soil whose influence on the thickness of the pavement thickness is (ITP = - 0.6665.6.16 + 8.4222 = 4.31) the same for all research points.